THE EFFECTIVENESS OF CONTENT-BASED INSTRUCTION TO TEACH SPEAKING VIEWED FROM STUDENTS’ CREATIVITY - Aisyah Sunarwan (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2014)
The objectives of the research are to examine: (1) whether Content-Based Instruction is more effective than Audio-Lingual Method to teach speaking to the third semester students of STAIN Jurai Siwo Metro in the academic year of 2012/2013; (2) whether the students having high creativity have better speaking skill than those having low creativity; and (3) whether there is an interaction between teaching methods and students’ creativity in teaching speaking. The method in this research was experimental study. It was conducted at the third semester students of STAIN Jurai Siwo Metro in the academic year of 2012/2013. The sample of the research was two classes; C consists of 40 students as an experimental class and E consists of 40 students as a control class. The sampling technique used was cluster random sampling. Each class was divided into two groups (the students having high and low creativity). The techniques of collecting data were creativity test and speaking test that were tried out to know their readability. The data were analyzed by using Multifactor Analysis of Variance (ANOVA) test of 2 x 2 and Tukey test.The result of data analysis shows that: (1) Content-Based Instruction is more effective than Audio-Lingual Method to teach speaking (2) the students having high creativity have better speaking skill than the students having low creativity and (3) there is an interaction between teaching methods and students’ creativity in teaching speaking. Based on the finding, it can be concluded that Content-Based Instruction is an effective method to teach speaking.